2016
DOI: 10.3892/mmr.2016.5756
|View full text |Cite
|
Sign up to set email alerts
|

CD38 gene-modified dendritic cells inhibit murine asthma development by increasing IL-12 production and promoting Th1 cell differentiation

Abstract: Predominant T helper (Th)2 and impaired Th1 cell polarization has a crucial role in the development of asthma. Cluster of differentiation (CD)38 is associated with the increased release of interleukin (IL)‑12 from dendritic cells (DCs) and DC‑induced Th1 cell polarization. However, whether CD38 expression affects DC function in asthma development remains unknown. In the current study, adenoviruses were constructed containing the murine CD38 gene. Overexpression of CD38 protein level in DCs induced from bone‑ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, a follow-up study highlighted that NK cell depletion in response to daratumumab treatment does not correlate with patient response [114], so more research is warranted in order to determine whether CD38+ NK cells are truly required for tumor elimination. Besides T cells and NK cells, CD38 is also expressed on dendritic cells and can induce a Th1 response [115,116], again highlighting a potentially anti-tumor immune population that may be inhibited with CD38 targeting As it stands, there are several areas of research necessitating further studies for better understanding of the impact of CD38 targeting in these tumors. Because CD38 functions on T cells, natural killer (NK) cells, and dendritic cells, anti-CD38 treatment may actually prevent the activity of these anti-tumor immune cells and thus decrease efficacy of this treatment strategy (yellow).…”
Section: Pro-and Antagonistic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a follow-up study highlighted that NK cell depletion in response to daratumumab treatment does not correlate with patient response [114], so more research is warranted in order to determine whether CD38+ NK cells are truly required for tumor elimination. Besides T cells and NK cells, CD38 is also expressed on dendritic cells and can induce a Th1 response [115,116], again highlighting a potentially anti-tumor immune population that may be inhibited with CD38 targeting As it stands, there are several areas of research necessitating further studies for better understanding of the impact of CD38 targeting in these tumors. Because CD38 functions on T cells, natural killer (NK) cells, and dendritic cells, anti-CD38 treatment may actually prevent the activity of these anti-tumor immune cells and thus decrease efficacy of this treatment strategy (yellow).…”
Section: Pro-and Antagonistic Effectsmentioning
confidence: 99%
“…However, a follow-up study highlighted that NK cell depletion in response to daratumumab treatment does not correlate with patient response [114], so more research is warranted in order to determine whether CD38+ NK cells are truly required for tumor elimination. Besides T cells and NK cells, CD38 is also expressed on dendritic cells and can induce a Th1 response [115,116], again highlighting a potentially anti-tumor immune population that may be inhibited with CD38 targeting and complicate treatment efficacy.…”
Section: Pro-and Antagonistic Effectsmentioning
confidence: 99%
“…Inhibition was a typical intervention effect and its stem “inhibit” was ranked in our results. For example, the following were included: the inhibition of glucocorticoids on degranulation of mast cells in allergic asthma [ 24 ], inhibition of the kinase ITK in a mouse model of asthma reduces cell death [ 25 ], and the inhibition of CD38 gene-modified dendritic cells on murine asthma development [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the corresponding experimental methods, some new techniques including digital droplet PCR (ddPCR) [ 111 ], whole-genome screen [ 112 ], and multiplexed fluorescent microsphere-based immunoassay (xMAP technology) [ 113 ] were widely adopted. Besides, a new type of cell was found in the list, dendritic cells [ 26 ], as one of the sentinel cells. Dendritic cells are the most important and primary antigen-presenting cells of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-λ1, also known as IL-29, is a newly-characterized member of the IFN-λ family and has the potential to decrease production of Th2 cytokines in vitro. 82 Li et al found that intranasal instillation of Ad-hIFN-λ1 prior to airway challenge in OVA-sensitized mice significantly decreased the severity of AHR, as well as eosinophil quantity and IL-4, IL-5, and IL-13 levels both in vivo and in vitro. Furthermore, Ad-hIFN-λ1 treatment inhibited serum IgE levels and increased the number of splenic CD4 + CD25 + FOXP3 + Treg cells.…”
Section: Overexpression Of Th1-stimulating Factors or Related Moleculesmentioning
confidence: 99%